2022
DOI: 10.1002/jor.25464
|View full text |Cite
|
Sign up to set email alerts
|

Potential for femoral size optimization for off‐the‐shelf implants: A CT derived implant database analysis

Abstract: In total knee arthroplasty, the femoral implant size is chosen mainly based on the femoral anteroposterior (AP) height and mediolateral (ML) width. This choice often is a compromise, due to limited size availability. Inadequate AP fit is expected to alter flexion laxity and thus knee function. Inadequate ML fit entails underhang or overhang, which is linked to worse clinical outcomes. Hence, we aimed to find implant size distributions, which maximize population coverage, and to evaluate the sensitivity regardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
(60 reference statements)
0
1
0
Order By: Relevance
“…In doing so, they addressed the limitations of the intraoperative measurements; however, evaluating over-/underhang only in a specific zone. In a previous study by our research group, an analysis of a database of 85,143 cases showed a population coverage of almost 85%, for an exemplary implant setup of 12 optimized implant sizes and error bounds of ±1.5 mm for anteroposterior (AP) and ±3 mm for mediolateral (ML) size fit (Grothues et al 2022). While only the total AP and ML dimensions were considered in this analysis, since they are regularly used for implant size selection, over-/underhang may occur along the entire bone-implant interface contour and should therefore be analyzed comprehensively.…”
Section: Introductionmentioning
confidence: 87%
“…In doing so, they addressed the limitations of the intraoperative measurements; however, evaluating over-/underhang only in a specific zone. In a previous study by our research group, an analysis of a database of 85,143 cases showed a population coverage of almost 85%, for an exemplary implant setup of 12 optimized implant sizes and error bounds of ±1.5 mm for anteroposterior (AP) and ±3 mm for mediolateral (ML) size fit (Grothues et al 2022). While only the total AP and ML dimensions were considered in this analysis, since they are regularly used for implant size selection, over-/underhang may occur along the entire bone-implant interface contour and should therefore be analyzed comprehensively.…”
Section: Introductionmentioning
confidence: 87%